From the sky down: Managing land use and soils towards net zero emissions - Wollenberg, Eva Karoline (2022)
"From the sky down: Managing land use and soils towards net zero emissions" was an introduction by moderator Lini Wollenberg at the January 25, 2022 Berlin Federal Ministry of Food & Agriculture and the Global Forum for Food & Agriculture -- session organized by the Organisation for Economic Co-operation and Development. She covered strategies to augment the world's terrestrial carbon sinks.